CT localization for a patient with a ground-glass opacity pulmonary nodule expecting thoracoscopy: a mixture of lipiodol and India ink - Kim, Kyung Soo; Beck, Kyongmin Sarah; Lee, Kyo Young; Moon, Seok Whan (Journal of Thoracic Disease, 2017)
Small and deeply seated pure ground-glass opacity (GGO) pulmonary nodules (PNs) are not discernible during video-assisted thoracoscopic surgery (VATS). Moreover, pathologists have difficulty in detecting these nodules due to insufficient localization. We percutaneously injected a mixture of lipiodol and India ink during preoperative CT-guided localization in a 52-year-old female patient presenting with a pure GGO PN. A black-pigmented tattoo lesion was clearly identified, and thoracoscopic wedge resection was performed without difficulty. Pathologic results were also discernible, thus allowing the target lesion to be identified without interruption for microscopic analysis. We introduce a novel method using a mixture of lipiodol and India ink with satisfactory results for preoperative localization of GGO PNs prior to VATS.